2014
DOI: 10.1074/jbc.m114.585315
|View full text |Cite|
|
Sign up to set email alerts
|

Thyroid Hormone Receptor Interacting Protein 13 (TRIP13) AAA-ATPase Is a Novel Mitotic Checkpoint-silencing Protein

Abstract: Background: How the mitotic checkpoint is silenced is not fully understood. Results: Interference with TRIP13 AAA-ATPase causes delayed activation of the anaphase-promoting complex/cyclosome and stalled metaphase-to-anaphase transition. Conclusion: TRIP13 is a novel mitotic checkpoint-silencing protein.Significance: TRIP13 overexpression may lead to premature chromosome segregation and chromosomal instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(155 citation statements)
references
References 70 publications
7
148
0
Order By: Relevance
“…These results clearly demonstrate that maintenance of the SAC is critical to prevent cancer formation. TRIP13 has been shown to promote the dissociation of the MCC complex (15)(16)(17), which subsequently inactivates the SAC to prevent the completion of mitosis (18). Thus, overexpression of TRIP13 and silencing of MCC components have similar effects on cells, since both can lead to dysregulation of the SAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results clearly demonstrate that maintenance of the SAC is critical to prevent cancer formation. TRIP13 has been shown to promote the dissociation of the MCC complex (15)(16)(17), which subsequently inactivates the SAC to prevent the completion of mitosis (18). Thus, overexpression of TRIP13 and silencing of MCC components have similar effects on cells, since both can lead to dysregulation of the SAC.…”
Section: Discussionmentioning
confidence: 99%
“…TRIP13 forms a stable hexameric ring, and ATP binding, as well as ATP hydrolysis, are critical for the function of the protein (13). Previous studies have revealed that TRIP13 is a novel component of the spindle assembly checkpoint (SAC) pathway (14)(15)(16)(17), which is crucial for the accurate distribution of duplicated chromosomes (18). Defects in the SAC pathway induce failure in chromosome separation and result in aneuploidy, which eventually leads to cellular apoptosis or transformation (19).…”
Section: Introductionmentioning
confidence: 99%
“…But recent attention has focused on mutual inhibition between the MCC and the APC/C (Reddy et al 2007), which requires a particular APC/C subunit, APC15 (Mansfeld et al 2011;Foster and Morgan 2012;Uzunova et al 2012). In animal cells, a second important player for MCC disassembly is the p31 comet protein (Habu et al 2002;Teichner et al 2011;Westhorpe et al 2011), which has recently been implicated in targeting an AAA ATPase to the MCC to initiate its disassembly (Eytan et al 2014;Wang et al 2014).…”
Section: The Biochemistry Of Mitosismentioning
confidence: 99%
“…Neither the role of AGS7/Trip13 as a regulator of the thyroid hormone receptor nor G protein signaling functions have been elucidated in the kidney in vivo. Instead, most of the work involving AGS7/Trip13, which is also a homolog to mouse pachytene checkpoint 2 (mPCH2), has focused on its AAAATPase activity with emphasis on the mechanistic control of DNA damage repair (Bolcun-Filas et al, 2014), cell-cycle checkpoint, kinetochore control (Tipton et al, 2012;Wang et al, 2014), and meiotic recombination (Li and Schimenti, 2007;Roig et al, 2010). These initial studies led to recent highimpact findings regarding AGS7/Trip13 in reproductive cell biology (Li and Schimenti, 2007;Roig et al, 2010) and cancer (Banerjee et al, 2014).…”
Section: Group III Ags Proteinsmentioning
confidence: 99%